EFL Pre-Service Teachers’ Experiences in Implementing Differentiated Instruction during Teaching Practice Program - Eka Fajar Rahmani; Dwi Riyanti; Kartika Yoga Eka Pratiwi Negara (Jurnal Pendidikan Progresif, 2024)
EFL Pre-Service Teachers’ Experiences in Implementing Differentiated Instruction during Teaching Practice Program.  This study explores the experiences of pre-service English teachers (PETs) in implementing Differentiated Instruction (DI) during their teaching practice in Indonesian junior and senior high schools. Using a qualitative descriptive approach, data were collected from 17 PETs who had completed their teaching practice, focusing on how they differentiated content, process, product, and the learning environment to meet diverse student needs. The findings reveal that PETs employed strategies such as scaffolding, flexible grouping, and offering multiple forms of assessment to address the range of linguistic competencies and learning styles among students. However, they also faced challenges, including time management, balancing diverse needs, student resistance to flexible grouping, assessing different products, limited resources, and maintaining student engagement. Despite these obstacles, PETs viewed DI as a valuable approach that enhanced their teaching effectiveness, though they recognized the need for more training and resources to implement it successfully. This study provides insights into the challenges and benefits of DI in pre-service teacher education, particularly within Indonesia’s Merdeka Curriculum. The implications suggest that teacher education programs should integrate more extensive DI training to better equip future teachers for diverse classroom dynamics. Limitations include the small sample size and focus on a specific context, which may limit generalizability. Future research should explore DI across different regions and school settings with larger samples. Keywords: differentiated instruction, pre-service teachers, ELT, teaching practice.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202490